Evaluation of the Air Pollution Mitigation Potential of Some Roadside Plants for Urban Forest Management - Mahrukh; Sohaib Muhammad; Muhammad Tayyab; Ali Ahmad; Zaher Uddin Babar; Nahaa M. Alotaibi; Muhammad Bilal; Amr Elkelish; Iqra Parvaz; Bushra Munam; Summiya Faisal; Muhammad Hasnain (Water, Air, & Soil Pollution, 2026)

New Fossils of Bovids (Bovidae, Mammalia) from the Siwaliks of Pakistan - Muhammad Akbar Khan; Khalid Mahmood; Saba Naz; Sayyed Ghyour Abbas; Muhammad Adeeb Babar; Mamoona Shahid (Geoheritage, 2026)

Meta-analytic evaluation of pyrethroid impacts on mammalian reproductive outcomes across 62 studies - Afzal Nimra; Mahnoor Usman; Javaireya Khan; Hanan Afzal; Amina Gull; Safdar Sidra; Ali Afzal; Muhammad Babar Khawar (Toxicology and Environmental Health Sciences, 2026)

Nanoparticles of thiolated gum ghatti for the controlled ocular delivery of Ciprofloxacin - Muhammad Abu Sufian; Shahid Shah; Akhtar Rasul; Nabeel Ahmad; Ghulam Abbas; Muhammad Hanif; Saleha Babar; Azka Fatima; Omeira Iqbal; Maira Tahir; Nader I. Namazi (DARU Journal of Pharmaceutical Sciences, 2026)

Biocultural structuring of ethnomedicinal knowledge across cultural and altitudinal gradients in the Western Himalayas - Choudhary Muhammad Babar; Sadaf Kayani; Musheerul Hassan; Ivana Vitasović-Kosić; Sayed Afzal Shah (Plant Biosystems, 2026)

Visual analytics of vaccine hesitancy: mapping sentiment and misinformation flows across digital ecosystems - Shahbaz Aslam; Sobia Abid; Arshad Ali; Babar Hussain; Muhammad Zahid Bilal (Next Research, 2026)

Antibacterial flavonoid derivatives: in silico ADMET, DFT, Molecular Docking, MD Simulation and in vitro verification - Atif Ishfaq; Affifa Tajammal; Riaz Maira; Aisha Waheed Qureshi; Babar Aleeza; Muhammad Asim Raza Basra (In Silico Pharmacology, 2026)

Unraveling the endocrine disruption potential of microplastics in testosterone regulation - Muhammad Babar Khawar; Ali Afzal; Kashifa Jalil; Tayyba Jan; Zaira Ahmad; Amna Rehman; Hanan Afzal; Sadia Ahmad; Afzal Nimra; Muhammad Ahsan Ashraf (Journal of Environmental Sciences, 2026)

Microplastics as Trojan horses: Vectors of pathogens, pollutants, and antimicrobial resistance genes - Ghazala Saeed; Ali Afzal; Afzal Nimra; Zaira Ahmad; Amna Rehman; Kaleem Maqsood; Tayyba Jan; Muhammad Ishfaq Ahmad; Naveed Karim; Byong-Hun Jeon; Ghulam Mustafa; Fakhar Zaman; et al. (Environmental Research, 2026)

Phosphorus-laden biochar modulates soil microbial communities and promotes phosphorus cycling in acidic soils - Zeinab El-Desouki; Yehia Abouseif; Jiyuan Wang; Muhammad Qasim; Saba Babar; Xiaoyang Xia; Xiangling Wang; Cuncang Jiang (Applied Soil Ecology, 2026)

Biochar mediated microbial responses to organic contaminants in soil environments: From mechanisms to ecological implications - Hao Zhu; Sami Ullah; Yuting Xu; Muhammad Salam; Silvia Celletti; Nadeem Iqbal; Muhammad Mohsin Raza; Babar Hussain; Palanisamy Vasudhevan (Applied Soil Ecology, 2026)

Enhanced Antimicrobial Photodynamic Effect Against Escherichia coli Using MXene-Based Silver–Curcumin 2D Nanocomposite Photosensitizers - Saliha Noor; Shahzad Anwar; Rafaqat Ali Khan; Sawera Malik; Hina Ali; Farwa Nurjis; Shaista Taimur; Muhammad Iftikhar; Muhammad Saleem; Babar Manzoor Atta (Journal of Fluorescence, 2026)

Hyaenodonta from the Middle to Late Miocene deposits of the Siwaliks of Pakistan with a brief account of Indian subcontinent hyaenodonts - Khalid Mahmood; Sayyed Ghyour Abbas; Steven E. Jasinski; Muhammad Adeeb Babar; Muhammad Akbar Khan (PalZ, 2026)
New fossil material identified as ‘creodonts,’ particularly hyaenodonts, from the Siwaliks of Pakistan provide significant new information on this important group of carnivores. Three hyaenodont taxa are identified based on these new fossils. Deciduous dental remains identified as ? Megistotherium/Hyainailouros sp. provide important new data on large hyaenodonts and their presence in the Miocene of southern Asia. Fossils identified as Hyaenodon cf. H . pervagus potentially provide important new temporal and biogeographic data on a highly speciose genus of hyaenodont. While the genus is known throughout much of the Northern Hemisphere (Asia, Europe, North America), these new fossils represent the first record of the genus from the Siwaliks, expanding its range in southern Asia. They also represent the youngest temporal occurrence of the genus (Middle Miocene). Another fossil represents a new species, Metapterodon anari sp. nov. This genus was previously tentatively identified from the Siwaliks, but this new material provides definitive evidence of its presence. Not only does this confirm its presence in the Miocene Siwalik deposits of the Indian subcontinent but also represents an important temporal occurrence for the genus. It represents the youngest occurrence of the genus worldwide but may also represent the youngest occurrence of any hyaenodont. The new material provides important new data on some of the less well-known ‘creodonts’ of the Siwaliks, and this data is important for not only our understanding of some of the youngest hyaenodonts near their eventual extinction, but the complex mammal communities preserved on the Indian subcontinent.

Paleodietary inferences of the Pleistocene (Pinjor Formation) ungulates from district Gujrat using mesowear analysis - Abrar Hussain; Muhammad Akbar Khan; Muhammad Asim; Sayyed Ghyour Abbas; Muhammad Adeeb Babar; Khalid Mahmood (Quaternary International, 2026)

Unearthing potential of aluminum-modified biochar for saline-alkali soil rejuvenation and microbial diversity enhancement - Saba BABAR; Amanullah BALOCH; Muhammad QASIM; Jiyuan WANG; Xiangling WANG; Rashid IQBAL; Ali M. ABD-ELKADER; Khurram SHEHZAD; Xiaoyang XIA; Cuncang JIANG (Pedosphere, 2026)

Green-synthesized nanoparticles used to restore soil health and reprogram plant resilience - Babar Iqbal; Inamullah; Amir Abdullah Khan; Ali Raza Khan; Rasheed Akbar; Muhammad Sohail Memon; Guanlin Li; Daolin Du (Journal of Environmental Chemical Engineering, 2026)

Decoding core molecular mechanisms of heat-stress tolerance in Brassica napus using transcriptomics and machine learning - Muhammad Ikram; Muhammad Farhan; Behnam Derakhshani; Sunjeet Kumar; Aliya Ayaz; Naveed Khan; Enerand Mackon; Babar Usman; Si Chengcheng; Pingwu Liu (Plant Cell Reports, 2026)

Formulation Design of Glucuronoxylan-Based Stimuli-Responsive Microparticles for Zero-Order Drug Delivery - Saleha Babar; Fatima Akbar Sheikh; Syed Nasir Abbas Bukhari; Muhammad Tahir Haseeb; Arshad Ali; Nisar Ul Khaliq; Ranya Abdulrahman Alafar; Mohamed Abdelwahab Abdelgawad; Ameeduzzafar Zafar; Naveed Ahmad (Journal of Pharmaceutical Innovation, 2026)

Impact of genetic composition on cows’ metabolic and fertility responses to thermal stress - Ihsan Ullah; Muhammad Subhan Qureshi; Raed M. Al-Atiyat; Shah Murad Khan; Ihtesham Ul Haq; Shabana Naz; Rifat Ullah Khan; Babar Maqbool; Marco Ragni; Ibrahim A. Alhidary (International Journal of Biometeorology, 2026)

Assessing sustainable performance using green entrepreneurial orientation, innovation, and technology dynamism: a study on Chinese manufacturing SMEs - Zuhaib Zafar; Li Wenyuan; Imran Khan; Suxia Liu; Muhammad Babar Iqbal (Clean Technologies and Environmental Policy, 2026)

New bovid fossils from the Dhok Pathan, Middle Siwalik subgroup of Pakistan - Kiran Aftab; Bilawal Ghafoor; Muhammad Akbar Khan; Muhammad Adeeb Babar; Mubashar Hussain; Shamaila Irum (PalZ, 2026)

Bisphenol S-induced endocrine disruption and reproductive anomalies - Benish Nawaz; Zaira Ahmad; Hanan Afzal; Kaleem Maqsood; Abdul Manan Khan; Zoya Asif; Sabahat Javed; Ali Afzal; Afzal Nimra; Muhammad Babar Khawar (Toxicology and Environmental Health Sciences, 2026)

Antibacterial Activity of Anthraquinones Isolated from Reynoutria Japonica Against Staphylococcus aureus: An in Silico and In Vitro Approach - Iqra Anam Khawaja; Sajid Ali; Muhammad Faheem; Syed Babar Jamal; Adnan Haider; Falak Niaz; Mi-Jeong Ahn; Mutiullah Khattak; Atif Ali Khan Khalil (Journal of Pharmaceutical Innovation, 2026)

The triple threat: the interwoven impact of climate vulnerability, income Inequality, and gender parity on educational access and outcomes - Samina Zamir; Muhammad Sajid Mehmood; Babar Nawaz Abbasi; Zhencun Wang (Environment, Development and Sustainability, 2026)

Tailoring of Cerium Oxide Nanosheets Having Superior Peroxidase Catalytic Activity for Colorimetric Detection of Hydrogen Peroxide - Mohib Ullah; Muhammad Aslam Khan; Sajid Ali; Asfandyar; Zeeshan Tahir; Muhammad Babar Saeed; Vineet Tirth; Ali Algahtani; Ruqia Nazir; Muslim Khan (Journal of Fluorescence, 2026)

Intensification of plasma process for the decomposition of p-xylene as a tar model compound to minimize the unwanted byproduct formation - Faisal Saleem; Muhammad Farooq; Azam Saeed; Shehzad Mustafa; Zaeem Bin Babar; Abdul Rehman; Syed Waqas Ahmad; Kui zhang; Adam Harvey (Fuel, 2026)

Interaction between biochar and nitrogen fertilizer improves nitrogen utilization efficiency, closely connected with rhizosphere microbes involved in nitrogen-cycling - Hao Xia; Jiyuan Wang; Muhammad Riaz; Saba Babar; Xiangling Wang; Xiaoyang Xia; Bohan Yan; Bo Liu; Cuncang Jiang (Soil and Tillage Research, 2025)

Exome sequencing in a Pakistani male infertility cohort: perspective on molecular diagnosis, genetic heterogeneity, and diagnostic yield - Dapeng Zhou; Ambrin Fatima; Afrasiab Ahmed; Tehseen Ullah Khan Afridi; Haq Nawaz Khan; Mussarat Ashraf; Muhammad Naeem; Syed Babar Jamal; Ishtiaq Hassan; Erica E. Davis; Feng Zhang; Rehana Rehman; et al. (Molecular Genetics and Genomics, 2025)

Comment on “The effect of colchicine on coagulation in patients with chronic coronary disease who use vitamin K antagonists” - Rayan Babar; Muhammad Hammad Chola; Hanzlah Ahmed (European Journal of Clinical Pharmacology, 2025)

Iron-modified biochar alleviates salt-alkali stress in cotton by enhancing iron availability and rhizosphere microbiome-metabolite interactions - Jiyuan Wang; Muhammad Riaz; Saba Babar; Xiangling Wang; Xiaoyang Xia; Bohan Yan; Cuncang Jiang (Plant and Soil, 2025)

Improvement in swell and consolidation behavior of sheard clay using glass powder and polypropylene fibers as additives - Syed Zishan Ashiq; Babar Naseem Khan Raja; Syed Minhaj Saleem Kazmi; Muhammad Junaid Munir; Muhammad Hassan (Innovative Infrastructure Solutions, 2025)

Effect of administration of flunixin meglumine on pregnancy and pregnancy loss rates after transfer of low-quality embryos in dromedary camels - Aly Karen; Muhammad Manzoor Ihsan; Muhammad Babar Ihsan; Raza Ur Rahman; Shanmugavelu Muthukumaran; Ahmed Abd-Elfattah (Small Ruminant Research, 2025)

Insight into amelioration effect of iron-modified biochar on saline-alkali soil chemical properties and bacterial communities along a soil depth gradient - Jiyuan WANG; Riaz MUHAMMAD; Saba BABAR; Zeinab El-DESOUKI; Yuxuan LI; Xiangling WANG; Xiaoyang XIA; Cuncang JIANG (Pedosphere, 2025)

New fossil Asian palm civets (Carnivora, Viverridae) from the Siwaliks of Pakistan - Sayyed Ghyour Abbas; Camille Grohé; Ari Grossman; Khalid Mahmood; Muhammad Adeeb Babar; Muhammad Akbar Khan (Geobios, 2025)

Inverse Analysis of Pressuremeter Tests by Calibrating Soil Parameters for Toronto Sands - Muhammad Salman Babar; Jinyuan Liu (Geotechnical and Geological Engineering, 2025)

Effects of chlorophenols on microbial activity and functional diversity: Recent advances in OMICs approaches and soil microbial remediation - Nadeem Iqbal; Muhammad Nauman; Babar Hussain; Sami Ullah; Palanisamy Vasudhevan; Dil Khurram; Riyazuddin Riyazuddin; Shengyan Pu (Applied Soil Ecology, 2025)

Retraction notice to “Template-based textural modifications of polymeric graphitic carbon nitrides towards waste water treatment” [Chemosphere 302, September 2022,134792] - Umair Azhar; Muhammad Sohail Bashir; Muhammad Babar; Muhammad Arif; Afaq Hassan; Asim Riaz; Rana Mujahid; Muhammad Sagir; Saadat Ullah Khan Suri; Pau Loke Show; Jo-Shu Chang; Kuan Shiong Khoo; et al. (Chemosphere, 2025)

Retraction notice to “Comparative study of ozonation and ozonation catalyzed by Fe-loaded biochar as catalyst to remove methylene blue from aqueous solution” [Chemosphere 307 Part 1, November 2022, 135738] - Muhammad Babar; Hafiz Muhammad Shahzad Munir; Aamna Nawaz; Naveed Ramzan; Umair Azhar; Muhammad Sagir; Muhammad Suleman Tahir; Amir Ikhlaq; Siti Nuurul huda Mohammad Azmin; Muhammad Mubashir; Kuan Shiong Khoo; Kit Wayne Chew (Chemosphere, 2025)

Microplastics and nanoplastics across the food web: Challenges and mitigation strategies in securing human health - Mingjun Chen; Ali Raza Khan; Muhammad Sohail Memon; Babar Iqbal (Process Safety and Environmental Protection, 2025)

Role of biochar in reducing polyethylene and polylactic acid microplastic co-contamination with antibiotics in soil-vegetable systems - Pengfei Cheng; Junliang Chen; Muhammad Tariq; Lei Tang; Zebin Hong; Babar Iqbal; Ismail Khan; Guanlin Li; Daolin Du; Tongxu Liu (Process Safety and Environmental Protection, 2025)

Crop Residue Management for Soil Health and Environmental Sustainability: A Comprehensive Review - Sadia Babar Baloch; Shahzaib Ali; Jaroslav Bernas; Petr Konvalina; Muhammad Naveed; Faryal Babar Baloch; Zameer Hussain Jamali; Tomáš Lošák; Hynek Roubík; Abdul Ghafoor; Mohsin Mehmood; Adnan Mustafa (Journal of Soil Science and Plant Nutrition, 2025)

The Effect of Native Plant Diversity on the Success of Invasive Species in Polluted Soils - Qaiser Javed; Jianfan Sun; Marko Černe; Babar Iqbal; Mohammed Bouhadi; David John Heath; Feng He; Muhammad Saif Ullah; Rasheed Akbar; Daolin Du (Ecotoxicology, 2025)

Rhizobacterial diversity exhibiting biotic stress tolerance in association with wheat-cotton crop rotation: Implications for plant–microbe interactions and agroecosystem resilience - Seema Aslam; Muhammad Babar; Ghulam Shabir; Tahir Naqqash; Florian M. W. Grundler (Biologia Futura, 2025)

Microbial transformation: the role of fermentation in advancing nutritional quality and human health - Babar Iqbal; Khulood Fahad Alabbosh; Abdulkareem Raheem; Inam Ullah; Ali Raza Khan; Muhammad Sohail Memon (Archives of Microbiology, 2025)

Beyond Data, Towards Sustainability: a Sydney Case Study On Urban Digital Twins - Ammar Sohail; Bojie Shen; Muhammad Aamir Cheema; Mohammed Eunus Ali; Anwaar Ulhaq; Muhammad Ali Babar; Asama Qureshi (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2025)
As urban areas grapple with unprecedented challenges stemming from population growth and climate change, the emergence of urban digital twins offers a promising solution. This paper presents a case study focusing on Sydney’s urban digital twin, a virtual replica integrating diverse real-time and historical data, including weather, crime, emissions, and traffic. Through visualization and data analysis techniques, the study explores some applications of this digital twin in urban sustainability, such as spatial ranking of suburbs and automatic identification of correlations between variables. Additionally, the research delves into predictive modeling, employing machine learning to forecast traffic crash risks using environmental data, showcasing the potential for proactive interventions. The contributions of this work lie in the comprehensive exploration of a city-scale digital twin for sustainable urban planning, offering a multifaceted approach to data-driven decision-making

Synthesis, biological evaluation, and in silico studies of chalcone-based ketamine derivatives with preferential COX-2 inhibitory activity - Syed Muzzammil Masaud; Humaira Nadeem; Abida Shamim; Muhammad Kazim Zargaham; Usman Shareef; Sana Ayaz; Babar Murtaza (Medicinal Chemistry Research, 2025)

Navigating soil microbiota shifts to organic pollutants: Insights into the roles of nZVI-biochar in soil ecosystem restoration - Sami Ullah; Babar Hussain; Nadeem Iqbal; Muhammad Salam; Muhammad Mohsin Raza; Shengyan Pu (Applied Soil Ecology, 2025)

Platelet-Rich Plasma (PRP) Mitigates Kidney Dysfunction in Alloxan-Induced Diabetic Mice via Modulation of Renal Iron Regulatory Genes - Humaira Allay Ali; Muddasir Hassan Abbasi; Tasleem Akhtar; Amin Arif; Mehreen Anjum; Sana Fatima; Rabia Mehmood; Adil Farooq; Nadeem Sheikh; Muhammad Babar Khawar (Biochemical Genetics, 2025)

Exploration of biochars for enhancing soil health, carbon sequestration, and greenhouse gas emission reductions under citrus cultivation - Muhammad Qasim; Saba Babar; Muhammad Usama Younas; Nimra Rajput; Xiaoyang Xia; Jiyuan Wang; Xiangling Wang; Cuncang Jiang (European Journal of Agronomy, 2025)

Rosmarinic acid attenuates photophobia, hyperalgesia and neuroinflammation during nitroglycerine induced migraine like headache in mice - Maira Anwar; Ismail Badshah; Babar Murtaza; Syed Muzzammil Masaud; Umair Ilyas; Amber Kiyani; Danish Patoli; Muhammad Tariq Khan (Natural Product Research, 2025)

Remediation of microplastics-contaminated agricultural soils by unmodified and modified biochar derived from Solidago canadensis L. - Babar Iqbal; Muhammad Junaid Nazir; Jiabao Lou; Yanjiao Wang; Eun Hea Jho; Mao Ye; Mingming Sun; Abdulkareem Raheem; Inamullah; Muhammad Sohail Memon; Guanlin Li; Xin Zhao; et al. (Process Safety and Environmental Protection, 2025)

Biochar amendment modulate microbial community assembly to mitigate saline-alkaline stress across soil depths - Xiangling Wang; Xiaoyang Xia; Muhammad Riaz; Saba Babar; Zeinab El-Desouki; Muhammad Qasim; Jiyuan Wang; Cuncang Jiang (Journal of Environmental Management, 2025)

Iron-modified biochar enhances cotton growth and iron uptake in saline-alkali soil by reducing salinity and facilitating root colonization of beneficial bacteria - Jiyuan Wang; Muhammad Riaz; Saba Babar; Zeinab El-Desouki; Yuxuan Li; Xiangling Wang; Xiaoyang Xia; Cuncang Jiang (Plant and Soil, 2025)

Unraveling the synergistic effect of biochar and potassium solubilizing bacteria on potassium availability and rapeseed growth in acidic soil - Saba Babar; Amanullah Baloch; Muhammad Qasim; Jiyuan Wang; Xiangling Wang; Ali M. Abd-Elkader; Zeinab El-Desouki; Xiaoyang Xia; Cuncang Jiang (Journal of Environmental Management, 2025)

Potential role of inoculum size in biomass accumulation and antioxidant secondary metabolites production in adventitious root cultures of Stevia rebaudiana - Naveed Ahmad; Nisar Ahmad; Muhammad Sajid; Kamran Rauf; Mudassar Iqbal; Muhammad Numan; Irfan Ullah; Amir Khan; Wahidah H. Al-Qahtani; Mostafa A. Abdel-Maksoud; Hamada AbdElgawad; Babar Iqbal; et al. (Plant Biosystems, 2025)

Genomic selection, gene editing, and reproductive biotechnology: a triad for the improvement of native buffalo breeds in a developing country perspective like Pakistan - Raja Danish Muner; Muhammad Moaeen-ud-Din; Ali Haider Saleem; Qudrat Ullah; Ghulam Abbas; Babar Maqbool; Masroor Ellahi Babar; Yanzhen Bi; Farhan Farooq (Tropical Animal Health and Production, 2025)

Extracellular lipase production from Bacillus cereus by using agro-industrial waste - Haniya Mazhar; Ali Afzal; Hanan Afzal; Amara Noureen; Muhammad Mubashir Iqbal Ahmad; Suneela Amaan; Naaz Abbas; Hongxin Zhu; Muhammad Babar Khawar (Biologia Futura, 2025)

Biomitigation of noxious metal ions using engineered lignin-based nanocomposites for sustainable environment - Zaeem Bin Babar; Rashid Iftikhar; Komal Rizwan; Shahid Munir; Mashhood Urfi; Fawad Ashraf; Muhammad Ali Inam; Shahid Iqbal; Muhammad Saad; Sajid Mahmood; Nasser S. Awwad; Hala A. Ibrahium (Journal of Water Process Engineering, 2025)

Equus remains from the Pleistocene deposits of Sardhok Pabbi Hills, Pakistan - Muhammad Akbar Khan; Kiran Aftab; Sayyed Ghyour Abbas; Muhammad Khaled Siddiq; Khalid Mahmood; Muhammad Adeeb Babar; Muhammad Akhtar (Geobios, 2025)

Unraveling insect feeding patterns and their ecological impacts on plant defense mechanisms - Arzlan Abbas; Muhammad Zulqar Nain Dara; Farman Ullah; Babu Saddam; Sohail Abbas; Aleena Alam; Mobeen Babar; Faisal Hafeez; Muhammad Dildar Gogi; Hamed A. Ghramh; Khalid Ali Khan; Yasir Niaz; et al. (Journal of Plant Diseases and Protection, 2025)

Effects of agricultural plastic films on crop growth and soil health in tobacco fields: A comparative study - Hao Xia; Jia Shen; Muhammad Riaz; Fafen Ran; Tingming Cheng; Xueying Wang; Qing Dong; Chaolong Zu; Bo Liu; Saba Babar; Chaoqiang Jiang (Applied Soil Ecology, 2025)

Potential of Lambda-Cyhalothrin for Controlling the Black Armyworm Spodoptera cosmioides (Walker) (Lepidoptera: Noctuidae): Toxicity and Midgut Histopathological Effects - Francelina Aparecida Duarte Rocha; Luis Carlos Martinez; Bárbara Soares Amoroso Lima; Cliver Fernandes Farder-Gomes; Jamile Fernanda Silva Cossolin; Muhammad Babar Shahzad Afzal; José Eduardo Serrão (Neotropical Entomology, 2025)

Effects of sublethal concentration of thiamethoxam formulation on the wild stingless bee, Partamona helleri Friese (Hymenoptera: Apidae): Histopathology, oxidative stress and behavioral changes - João Victor de Oliveira Motta; Davy Soares Gomes; Laryssa Lemos da Silva; Mateus Soares de Oliveira; Daniel Silva Sena Bastos; Matheus Tudor Cândido Santos Resende; Jéssica Roberta Lacerda Alvim; Aline Beatriz Reis; Leandro Licursi de Oliveira; Muhammad Babar Shahzad Afzal; José Eduardo Serrão (Science of The Total Environment, 2024)

Unlocking plant resilience: Advanced epigenetic strategies against heavy metal and metalloid stress - Babar Iqbal; Naveed Ahmad; Guanlin Li; Arshad Jalal; Ali Raza Khan; Xiaojun Zheng; Muhammad Naeem; Daolin Du (Plant Science, 2024)

Catalytic strategies for CO2 hydrogenation to BTX and p-xylene: A sustainable approach towards carbon neutrality - Babar Ali; Muhammad Tahir Arslan; Ijaz Hussain; Yahuza Nantomah Abdulai; Khalid Alhooshani; Saheed Adewale Ganiyu (Journal of Environmental Chemical Engineering, 2024)

Enabling Spatial Digital Twins: Technologies, Challenges, and Future Research Directions - Mohammed Eunus Ali; Muhammad Aamir Cheema; Tanzima Hashem; Anwaar Ulhaq; Muhammad Ali Babar (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2024)

Sirtuin insights: bridging the gap between cellular processes and therapeutic applications - Shagufta Kamal; Sharon Babar; Waqas Ali; Kanwal Rehman; Amjad Hussain; Muhammad Sajid Hamid Akash (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Diagnostic and therapeutic value of EVs in lungs diseases and inflammation - Ali Afzal; Muhammad Babar Khawar; Ume Habiba; Hanan Afzal; Syeda Eisha Hamid; Mussarat Rafiq; Muddasir Hassan Abbasi; Nadeem Sheikh; Rimsha Abaidullah; Zoya Asif; Tahaa Saeed (Molecular Biology Reports, 2024)

Detection and monitoring techniques of termites in buildings: A review - Babar Hassan; Muhammad Achirul Nanda (International Biodeterioration & Biodegradation, 2024)

Environmental Heavy Metal Exposure and Associated Cardiovascular Diseases in Light of the Triglyceride Glucose Index - Muhammad Bilal Sardar; Mohsin Raza; Ammara Fayyaz; Muhammad Asfandyar Nadir; Zain Ali Nadeem; Muhammad Babar (Cardiovascular Toxicology, 2024)

Microplastic and cadmium contamination: Impact on the soil by inhibiting the growth of pak choi (Brassica rapa subsp. chinensis) - Guanlin Li; Xinran Cui; Muhammad Tariq; Ismail Khan; Ali Raza Khan; Sami Al Obaid; Mohammad Javed Ansari; Huan Zhou; Babar Iqbal; Xin Zhao (Process Safety and Environmental Protection, 2024)

Metabolites-induced co-evolutionary warfare between plants, viruses, and their associated vectors: So close yet so far away - Naveed Ahmad; Hamad Hussain; Muhammad Naeem; Saeed ur Rahman; Khalid Ali Khan; Babar Iqbal; Abdul Wakeel Umar (Plant Science, 2024)

Effect of zinc fortified, arid and irrigated wheat varieties flour upon life history parameters of red flour beetle, Tribolium castaneum (Herbest) (Coleoptera: Tenebrionidae) - Muhammad Rizwan; Muhammad Yasin; Muhammad Tahir; Ammad Ahmad; Ansa Banazeer; Muhammad Babar Shahzad Afzal; Umair Sagheer (Journal of Stored Products Research, 2024)

Co-application of biochar and potassium fertilizer improves soil potassium availability and microbial utilization of organic carbon: A four-year study - Hao Xia; Jiyuan Wang; Muhammad Riaz; Saba Babar; Yuxuan Li; Xiangling Wang; Xiaoyang Xia; Bo Liu; Cuncang Jiang (Journal of Cleaner Production, 2024)

Uptake, Agglomeration, and Detoxification of Trace Metals and Metalloids in Plants - Babar Hussain; Aqleem Abbas; Aansa Rukya Saleem; Luqman Riaz; Shafeeq Ur Rahman; Shibin Liu; Shengyan Pu; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2024)

An integrated model with interdependent water storage for optimal resource management in Energy–Water–Food Nexus - Muhammad Babar Rasheed; María D. R-Moreno (Journal of Cleaner Production, 2024)

Lophochoerus nagrii (Suidae) from the Siwaliks (Neogene) of Pakistan - Muhammad Adeeb Babar; Sayyed Ghyour Abbas; Muhammad Akbar Khan; Muhammad Akhtar (Annales de Paléontologie, 2024)

Molecular mechanisms of morphine tolerance and dependence; novel insights and future perspectives - Ismail Badshah; Maira Anwar; Babar Murtaza; Muhammad Imran Khan (Molecular and Cellular Biochemistry, 2024)

Acid-modified cotton straw biochar has instructive for the improvement of saline-alkali soil - Xiaoyang Xia; Muhammad Riaz; Saba Babar; Yuxuan Li; Xiangling Wang; Jiyuan Wang; Cuncang Jiang (Journal of Soils and Sediments, 2024)

RETRACTED ARTICLE: Multifaceted role of TRIM21 in inflammation - Sana Tanveer; Ali Afzal; Zaman Gul; Hanan Afzal; Amara Noureen; Muhammad Sharif; Muhammad Babar Khawar (Biologia Futura, 2024)

Soil microplastics: Impacts on greenhouse gasses emissions, carbon cycling, microbial diversity, and soil characteristics - Ismail Khan; Muhammad Tariq; Khulood Fahad Alabbosh; Abdul Rehman; Abdul Jalal; Asif Ali Khan; Muhammad Farooq; Guanlin Li; Babar Iqbal; Naveed Ahmad; Khalid Ali Khan; Daolin Du (Applied Soil Ecology, 2024)

Alleviation of cotton growth suppression caused by salinity through biochar is strongly linked to the microbial metabolic potential in saline-alkali soil - Xiangling Wang; Muhammad Riaz; Xiaoyang Xia; Saba Babar; Zeinab El-Desouki; Yuxuan Li; Jiyuan Wang; Cuncang Jiang (Science of The Total Environment, 2024)

Middle Miocene “Giraffa” from the Chinji Formation of Siwaliks, Pakistan - Muhammad Asim; Kiran Aftab; Muhammad Akbar Khan; Sayyed Ghyour Abbas; Muhammad Adeeb Babar; Mubashar Hussain; Sania Saeed (Palaeoworld, 2024)

Harnessing soil carbon sequestration to address climate change challenges in agriculture - Muhammad Junaid Nazir; Guanlin Li; Muhammad Mudassir Nazir; Faisal Zulfiqar; Kadambot H.M. Siddique; Babar Iqbal; Daolin Du (Soil and Tillage Research, 2024)

Spatio-temporal variations in dissolved trace elements in peat bog porewaters impacted by dust inputs from open-pit mining activities in the Athabasca Bituminous Sands (ABS) region - Sundas Arooj Butt; Fiorella Barraza; Kevin Devito; Lukas Frost; Muhammad Babar Javed; Tommy Noernberg; Andrii Oleksandrenko; William Shotyk (Environmental Pollution, 2024)

Microplastic contamination in the agricultural soil—mitigation strategies, heavy metals contamination, and impact on human health: a review - Muhammad Tariq; Babar Iqbal; Ismail Khan; Ali Raza Khan; Eun Hea Jho; Abdul Salam; Huan Zhou; Xin Zhao; Guanlin Li; Daolin Du (Plant Cell Reports, 2024)

Spatial variation and chemical reactivity of dusts from open-pit bitumen mining using trace elements in snow - Fiorella Barraza; Muhammad Babar Javed; Tommy Noernberg; Judy Schultz; William Shotyk (Chemosphere, 2024)

Alterations in the composition and metabolite profiles of the saline-alkali soil microbial community through biochar application - Xiangling Wang; Muhammad Riaz; Saba Babar; Zeinab Eldesouki; Bo Liu; Hao Xia; Yuxuan Li; Jiyuan Wang; Xiaoyang Xia; Cuncang Jiang (Journal of Environmental Management, 2024)

Glucose input profit soil organic carbon mineralization and nitrogen dynamics in relation to nitrogen amended soils - Muhammad Junaid Nazir; Muhammad Mahroz Hussain; Gadah Albasher; Babar Iqbal; Khalid Ali Khan; Riffat Rahim; Guanlin Li; Daolin Du (Journal of Environmental Management, 2024)

Barriers affecting implementation of life cycle cost analysis in construction projects: SEM approach - Muhammad Altaf; Wesam Salah Alaloul; Muhammad Ali Musarat; Sherif Mostafa; Rodney Stewart; Ali Hussain; Muhammad Babar Ali Rabbani; Syed Saad; Syed Ammad (Innovative Infrastructure Solutions, 2024)

Phytotoxicity of radionuclides: A review of sources, impacts and remediation strategies - Shahzaib Ali; Sadia Babar Baloch; Jaroslav Bernas; Petr Konvalina; Eze Festus Onyebuchi; Muhammad Naveed; Hassan Ali; Zameer Hussain Jamali; Mohammad Tahsin Karimi Nezhad; Adnan Mustafa (Environmental Research, 2024)

Black carbon emissions inventory and scenario analysis for Pakistan - Kaleem Anwar Mir; Pallav Purohit; Muhammad Ijaz; Zaeem Bin Babar; Shahbaz Mehmood (Environmental Pollution, 2024)

Emerging role of lipophagy in liver disorders - Bismillah Nazeer; Muhammad Babar Khawar; Muhammad Usman Khalid; Syeda Eisha Hamid; Mussarat Rafiq; Muddasir Hassan Abbasi; Nadeem Sheikh; Ahmad Ali; Hooriya Fatima; Sadia Ahmad (Molecular and Cellular Biochemistry, 2024)

Effect of co-application of straw and various nitrogen fertilizers on N2O emission in acid soil - Yuxuan Li; Riaz Muhammad; Babar Saba; Hao Xia; Xiangling Wang; JiYuan Wang; Xiaoyang Xia; Jiang Cuncang (Journal of Environmental Management, 2023)

Abiogenic silicon: Interaction with potentially toxic elements and its ecological significance in soil and plant systems - Babar Hussain; Luqman Riaz; Kun Li; Kashif Hayat; Naveed Akbar; Muhammad Zakwan Hadeed; Bowei Zhu; Shengyan Pu (Environmental Pollution, 2023)

Melatonin-induced development of adventitious roots, biosynthesis of secondary cell products and greener synthesis of silver nanoparticles for biological activities using Indigofera heterantha - Irfan Ullah; Muhammad Sajid; Nisar Ahmad; Naveed Ahmad; Kamran Rauf; Rabia Khalil; Babar Iqbal; Mazhar Ali; Marcelo Carvalho Minhoto Teixeira Filho; Mohammad K. Okla; Hamada AbdElgawad; Asghar Khan; et al. (South African Journal of Botany, 2023)

“ Assessing the impact of biochar on microbes in acidic soils: Alleviating the toxicity of aluminum and acidity” - Hao Xia; Muhammad Riaz; Saba Babar; Lei Yan; Yuxuan Li; Xiangling Wang; Jiyuan Wang; Cuncang Jiang (Journal of Environmental Management, 2023)

Efficient degradation and mineralization of aniline in aqueous solution by new dielectric barrier discharge non-thermal plasma - Muhammad Imran Nawaz; Chengwu Yi; Abdul Mannan Zafar; Rongjie Yi; Babar Abbas; Husseini Sulemana; Chundu Wu (Environmental Research, 2023)

Natural enrichment of Cd and Tl in the bark of trees from a rural watershed devoid of point sources of metal contamination - William Shotyk; Fiorella Barraza; Chad W. Cuss; Iain Grant-Weaver; Carla Germani; Muhammad Babar Javed; Stephen Hillier; Tommy Noernberg; Andrii Oleksandrenko (Environmental Research, 2023)

Biogenic adsorbents for removal of drugs and dyes: A comprehensive review on properties, modification and applications - Mobeen Ur Rehman; Muhammad Babar Taj; Sónia A.C. Carabineiro (Chemosphere, 2023)

Assessing Household’s Municipal Waste Segregation Intentions in Metropolitan Cities of Pakistan: A Structural Equation Modeling Approach - Tanzila Akmal; Faisal Jamil; Muhammad Haseeb Raza; Cosimo Magazzino; Babar Hussain (Environmental Monitoring and Assessment, 2023)
There is a growing concern about inappropriate waste disposal and its negative impact on human health and the environment. The objective of this study is to understand household waste segregation intention considering psychological, institutional, and situational factors simultaneously. Insights into the motivations of household waste segregation drivers may assist in a better knowledge of how to pursue the most efficient and effective initiatives. For this purpose, data from a representative sample comprising 849 households is obtained from the twin cities of Islamabad and Rawalpindi (Pakistan). The empirical analysis employs a Structural Equation Modeling (SEM) approach, showing that policy instruments have significant direct and indirect impacts on households’ segregation intentions. The results highlight that government policy instruments strengthen personal and perceived norms for waste segregation intentions, resulting in an external intervention that would encourage intrinsic motivation. Therefore, policy actions become the main entry point for initiating waste segregation behavior. Public policy must continue to emphasize waste segregation since it may help resource recovery. This is imperative because the environment is a shared resource, and its conservation increases social welfare.

Gum-based nanocomposites for the removal of metals and dyes from waste water - Muhammad Usman; Muhammad Babar Taj; Sónia Alexandra Correia Carabineiro (Environmental Science and Pollution Research, 2023)
The importance of water for all living organisms is unquestionable and protecting its sources is crucial. In order to reduce water contaminants, like toxic metals and organic dyes, researchers are exploring different techniques, such as adsorption, photocatalytic degradation, and electrolysis. Novel materials are also being sought. In particular, biopolymers like guar gum and xanthan gum, that are eco-friendly, non-toxic, reusable, abundant and cost-effective, have enormous potential. Gum-based nanocomposites can be prepared and used for removing heavy metals and colored dyes by adsorption and degradation, respectively. This review explains the significance of gum-based nanomaterials in waste water treatment, including preparative steps, characterization techniques, kinetics models, and the degradation and adsorption mechanisms involved.

Influence of soil microplastic contamination and cadmium toxicity on the growth, physiology, and root growth traits of Triticum aestivum L. - Babar Iqbal; Qaiser Javed; Ismail Khan; Muhammad Tariq; Naveed Ahmad; Hosam O. Elansary; Arshad Jalal; Guanlin Li; Daolin Du (South African Journal of Botany, 2023)

Effect of heterologous platelet-rich plasma on liver and modulation of glucose metabolism and Wnt signalling pathways in diabetic mice - Amin Arif; Adil Farooq; Muddasir Hassan Abbasi; Muhammad Babar Khawar; Tasleem Akhtar; Humaira Allay Ali; Mehreen Anjum; Rabia Mehmood; Tayyaba Saleem; Nadeem Sheikh (Molecular Biology Reports, 2023)

Cadmium Prevalence in Cacao (Theobroma cacao L.) and Potential Remediation Strategies - Babar Hussain; Shibin Liu; Shafeeq Ur Rahman; Santos Triunfo Leiva-Espinoza; Khadija Javed; Shengyan Pu; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2023)

Quality Analysis of Canola and Mustard Oil Using Fluorescence Spectroscopy - Muhammad Saleem; Hina Ali; M. Bilal; Babar M. Atta; Naveed Ahmad (Journal of Fluorescence, 2023)

Correction: KASP mapping of QTLs for yield components using a RIL population in Basmati rice (Oryza sativa L.) - Hamza Ashfaq; Reena Rani; Naila Perveen; Allah Ditta Babar; Umer Maqsood; Muhammad Asif; Katherine A. Steele; Muhammad Arif (Euphytica, 2023)

Microplastics: unraveling the signaling pathways involved in reproductive health - Muhammad Tanveer; Nimra Mansha; Afzal Nimra; Muhammad Babar Khawar; Ali Afzal; Hanan Afzal; Muhammad Farooq; Sadia Ehsan; Rabbia Rana; Sara Shahzaman (Environmental Science and Pollution Research, 2023)

Engineering legumes for drought stress tolerance: Constraints, accomplishments, and future prospects - Arshad Jalal; Kamran Rauf; Babar Iqbal; Rabia Khalil; Hayat Mustafa; Muhammad Murad; Farhan Khalil; Sulaiman Khan; Carlos Eduardo da Silva Oliveira; Marcelo Carvalho Minhoto Teixeira Filho (South African Journal of Botany, 2023)

Can the co-application of biochar and different inorganic nitrogen fertilizers repress N2O emissions in acidic soil? - Yuxuan Li; Riaz Muhammad; Babar Saba; Hao Xia; Xiangling Wang; JiYuan Wang; Cuncang Jiang (Environmental Research, 2023)

Recent advances to Neuroprotection: repurposing drugs against neuroinflammatory disorders - Wishah Bilal; Muhammad Babar Khawar; Ali Afzal; Arshia Naseer; Syeda Eisha Hamid; Sara Shahzaman; Fareeha Qamar (Molecular Biology Reports, 2023)

KASP mapping of QTLs for yield components using a RIL population in Basmati rice (Oryza sativa L.) - Hamza Ashfaq; Reena Rani; Naila Perveen; Allah Ditta Babar; Umer Maqsood; Muhammad Asif; Katherine A. Steele; Muhammad Arif (Euphytica, 2023)
Super Basmati is an elite variety with extra-long grains and superior quality but its yield is severely affected by water stress. Recombinant inbred lines (RILs) developed from the cross of Super Basmati and IR55419-04 (a coarse grained variety with high yield potential) were used to identify and map yield-related quantitative trait loci (QTLs) under normal field conditions. Genotypes for 244 KASP markers were obtained from 188 F 9 RILs and a linkage map constructed of 1369.4 cM, with average marker interval of 10.5 cM. Eleven agronomic traits were phenotyped in RILs and parents. Composite interval mapping and inclusive composite interval mapping model identified 21 common QTLs related to nine agronomic traits; of the QTLs identified, twelve mapped at novel positions. LOD scores ranged from 2.51 for number of filled grains ( qFG1.1 ) to 16.8 for plant height ( qPH1.1 ). Four major effect QTLs could explain 20% of variation related for plant height, hundred-grain weight and grain width. Alleles from IR55419-04 improved grain filling, grain weight and grain width, while alleles from Super Basmati contributed to longer grains, panicles and flag leaves. Putative candidate genes were identified for 18 yield-related QTLs. These results validate the use of KASP genotyping for QTL mapping of yield-related traits in a bi-parental segregating population. SNPs in the QTLs identified in this study can be used in marker assisted selection for yield components to improve Basmati rice.

Iron-modified biochar reduces nitrogen loss and improves nitrogen retention in Luvisols by adsorption and microbial regulation - Jiyuan Wang; Muhammad Riaz; Saba Babar; Hao Xia; Yuxuan Li; Xiaoyang Xia; Xiangling Wang; Cuncang Jiang (Science of The Total Environment, 2023)

Unraveling the functional characterization of a jasmonate-induced flavonoid biosynthetic CYP45082G24 gene in Carthamus tinctorius - Yufei Wang; Zhiling Li; Naveed Ahmad; Xiaoxiao Sheng; Babar Iqbal; Muhammad Naeem; Nan Wang; Fengwei Li; Na Yao; Xiuming Liu (Functional & Integrative Genomics, 2023)

Effect of type and volume fraction of recycled-tire steel fiber on durability and mechanical properties of concrete - Babar Ali; Muhammad Ahmad Farooq; Rawaz Kurda; Rayed Alyousef; Muhammad Noman; Hisham Alabduljabbar (European Journal of Environmental and Civil Engineering, 2023)

Graphene loaded TiO2 submicron spheres scattering layer for efficient dye-sensitized solar cell - Muhammad Umair Shahid; Norani Muti Mohamed; Ali Samer Muhsan; Siti Nur Azella Zaine; Mehboob Khatani; Asfand Yar; Waqar Ahmad; Muhammad Babar Hussain; Asma A. Alothman; Mohammed Sheikh Saleh Mushab (Chemosphere, 2023)

Performance evaluation of phosphonium based deep eutectic solvents coated cerium oxide nanoparticles for CO2 capture - Tausif Ahmad; Jibran Iqbal; Mohamad Azmi Bustam; Muhammad Babar; Muhammad Bilal Tahir; Muhammad Sagir; Muhammad Irfan; Hafiz Muhammad Anwaar Asghar; Afaq Hassan; Asim Riaz; Lai Fatt Chuah; Awais Bokhari; et al. (Environmental Research, 2023)

Diversity of hipparionines (Perissodactyla: Equidae) from the late Miocene–Pliocene Siwalik deposits at Haritalyangar, India - Anek Ram Sankhyan; Sayyed Ghyour Abbas; Muhammad Akbar Khan; Muhammad Adeeb Babar; Amir Yasin (Annales de Paléontologie, 2023)

Role of financial development, foreign direct investment inflow, innovation in environmental degradation in Pakistan with dynamic ARDL simulation model - Ali Jan; Zhao Xin-gang; Samreen Fahim Babar; Muhammad Kamran Khan (Environmental Science and Pollution Research, 2023)

High pressure CO2 adsorption onto Malaysian Mukah-Balingian coals: Adsorption isotherms, thermodynamic and kinetic investigations - Mustafa Abunowara; Mohamad Azmi Bustam; Suriati Sufian; Muhammad Babar; Usama Eldemerdash; Ahmad Mukhtar; Sami Ullah; Mohammed Ali Assiri; Abdullah G. Al-Sehemi; Su Shiung Lam (Environmental Research, 2023)

Evaluating adoption of climate smart agricultural practices among farmers in the Fujian Province, China - Rao Sabir Sattar; Muhammad Sajid Mehmood; Muhammad Hammad Raza; V. P. I. S. Wijeratne; Babar Shahbaz (Environmental Science and Pollution Research, 2023)

Rational design and modulation strategies of Mo-based electrocatalysts and photo/electrocatalysts towards nitrogen reduction to ammonia (NH3) - Muhammad Arif; Muhammad Babar; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Asim Mushtaq; Ghulam Yasin; Muhammad Mubashir; Jun Wei Roy Chong; Kuan Shiong Khoo; Pau Loke Show (Chemical Engineering Journal, 2023)

Plant Growth-Promoting Rhizobacteria Significantly Improves Growth Attributes and Photosynthetic Machinery in Wheat - Tahir Naqqash; Mahreen Fatima; Saif-ur-Rehman; Sherien Bukhat; Muhammad Shahid; Ghulam Shabir; Muhammad Tahir; Muhammad Arshad; Muhammad Babar (Journal of Plant Growth Regulation, 2022)

Leaf Area Regulates the Growth Rates and Seed Yield of Soybean (Glycine max L. Merr.) in Intercropping System - Muhammad Ali Raza; Hina Gul; Ali Hasnain; Muhammad Hayder Bin Khalid; Sajad Hussain; Ghulam Abbas; Waqas Ahmed; Muhammad Jawad Babar; Zaheer Ahmed; Amjad Saeed; Muhammad Umair Riaz; Azeem Iqbal Khan; et al. (International Journal of Plant Production, 2022)

Correction to: Mechanical performance and environmental impact of normal strength concrete incorporating various levels of coconut fiber and recycled aggregates - Syed Haroon Ali Shah; Muhammad Talha Amir; Babar Ali; Mohamed Hechmi El Ouni (Environmental Science and Pollution Research, 2022)

Bisphenol S induced dysregulations in liver; iron regulatory genes and inflammatory mediators in male Wistar rats - Shazia Ghafoor; Muddasir Hassan Abbasi; Muhammad Babar Khawar; Asima Tayyeb; Tayyaba Saleem; Isbah Ashfaq; Nadeem Sheikh (Environmental Science and Pollution Research, 2022)

Mechanical performance and environmental impact of normal strength concrete incorporating various levels of coconut fiber and recycled aggregates - Syed Haroon Ali Shah; Muhammad Talha Amir; Babar Ali; Mohamed Hechmi El Ouni (Environmental Science and Pollution Research, 2022)

Sulfur concrete made with waste marble and slag powders: 100% recycled and waterless concrete - Muhammad Faisal Rasheed; Abdur Rahim; Muhammad Irfan-ul-Hassan; Babar Ali; Nazam Ali (Environmental Science and Pollution Research, 2022)

Bacterial Redox Cycling of Manganese in Calcareous Soil Enhances the Nutrients Bioavailability to Wheat - Saba Babar; Ghulam Jilani; Adil Mihoub; Aftab Jamal; Iftikhar Ahmad; Arshad Nawaz Chaudhary; Muhammad Farhan Saeed; Tajwar Alam (Journal of Soil Science and Plant Nutrition, 2022)

Development of Basmati lines by the introgression of three bacterial blight resistant genes through marker-assisted breeding - Allah Ditta Babar; Abha Zaka; Shahzad Amir Naveed; Niaz Ahmad; Kashif Aslam; Muhammad Asif; Umer Maqsood; Casiana M. Vera Cruz; Muhammad Arif (Euphytica, 2022)

Status of insecticide resistance in Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae) from 1997 to 2019: cross-resistance, genetics, biological costs, underlying mechanisms, and implications for management - Ansa Banazeer; Muhammad Babar Shahzad Afzal; Shoaib Hassan; Mamuna Ijaz; Sarfraz Ali Shad; José Eduardo Serrão (Phytoparasitica, 2022)

Baseline toxicity of ten insecticides from organophosphate, pyrethroid and novel mode of action groups against Droschica mangiferae (Homoptera: Margarodidae) collected from citrus orchard in 2017–19 - Muhammad Nawaz Khan; Muhammad Babar Shahzad Afzal; Naima Din; Afifa Naeem; Ansa Banazeer; Malik Abdul Rehman; Hira Tariq; Muhammad Raza Salik; Muhammad Qasim (International Journal of Tropical Insect Science, 2022)

Diagnostic, prognostic and therapeutic potential of long noncoding RNAs in cancer - Muhammad Babar Khawar; Syeda Eisha Hamid; Tayyba Jan; Muddasir Hassan Abbasi; Muhammad Idnan; Nadeem Sheikh (Molecular Biology Reports, 2022)

High-fat diet intake ameliorates the expression of hedgehog signaling pathway in adult rat liver - Rabia Mehmood; Nadeem Sheikh; Muhammad Babar Khawar; Muddasir Hassan Abbasi; Maryam Mukhtar (Molecular Biology Reports, 2022)

Range extension and species confirmation of Rhyneptesicus nasutus (Sind Serotine Bat) (Mammalia:Chiroptera) from Bajaur Agency, FATA, Pakistan - Muhammad Idnan; Sajid Mansoor; Muhammad Babar Khawar; Arshad Javid; Ali Hussain; Muhammad Imran; Arif Ullah (Molecular Biology Reports, 2022)

Biochemical resistance characterization to chlorpyrifos, acetamiprid, spinosad, and emamectin benzoate in Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) from Pakistan - Bushra Saddiq; Muhammad Babar Shahzad Afzal; Ashfaq Ahmad Sial; Naeem Abbas; Sarfraz Ali Shad; Asif Sajjad; Sajjad Ali (Phytoparasitica, 2022)

Role of financial development, environmental-related technologies, research and development, energy intensity, natural resource depletion, and temperature in sustainable environment in Canada - Muhammad Kamran Khan; Samreen Fahim Babar; Bahareh Oryani; Vishal Dagar; Abdul Rehman; Abdulrasheed Zakari; Muhammad Owais Khan (Environmental Science and Pollution Research, 2022)

Quantifying climate-induced drought risk to livelihood and mitigation actions in Balochistan - Muhammad Ashraf; Adnan Arshad; Praharsh M. Patel; Adeel Khan; Huma Qamar; Ristina Siti-Sundari; Muhammad Usman Ghani; Ali Amin; Jamilur Rehman Babar (Natural Hazards, 2021)

Lack of CpG islands in human unitary pseudogenes and its implication - Ammad Aslam Khan; Muhammad Shahryar Ali; Farah Babar; Anees Fatima; Muhammad Awais Shafqat; Bisma Asghar; Nimra Ilyas; Maheen Fatima; Ayesha Liaqat; Muhammad Aslam Gondal (Mammalian Genome, 2021)

Soil microbial biomass and extracellular enzyme–mediated mineralization potentials of carbon and nitrogen under long-term fertilization (> 30 years) in a rice–rice cropping system - Muhammad Nadeem Ashraf; Gao Jusheng; Wu Lei; Adnan Mustafa; Ahmed Waqas; Tariq Aziz; Waqas-ud-Din Khan; Shafeeq-ur-Rehman; Babar Hussain; Muhammad Farooq; Zhang Wenju; Xu Minggang (Journal of Soils and Sediments, 2021)

Tetraconodon and Sivachoerus (Suidae) from Dhok Pathan and Hasnot area of Potwar Plateau, northern Pakistan - Muhammad Adeeb Babar; Kiran Aftab; Muhammad Akbar Khan; Sayyad Ghyour Abbas; Muhammad Asim; Muhammad Akhtar (Arabian Journal of Geosciences, 2021)

High-fat diet-induced splenic, hepatic, and skeletal muscle architecture damage: cellular and molecular players - Ambreen Asghar; Tasleem Akhtar; Tayyeba Batool; Muhammad Babar Khawar; Sania Nadeem; Rabia Mehmood; Nadeem Sheikh (Molecular and Cellular Biochemistry, 2021)

In Silico Mutagenesis-Based Remodelling of SARS-CoV-1 Peptide (ATLQAIAS) to Inhibit SARS-CoV-2: Structural-Dynamics and Free Energy Calculations - Abbas Khan; Shaheena Umbreen; Asma Hameed; Rida Fatima; Ujala Zahoor; Zainib Babar; Muhammad Waseem; Zahid Hussain; Muhammad Rizwan; Nasib Zaman; Shahid Ali; Muhammad Suleman; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2021)

New remains of Gazella (Bovidae) from Middle Miocene, Pakistan - Muhammad Akbar Khan; Muhammad Asim; Muhammad Adeeb Babar; Sayyed Ghyour Abbas; Muhammad Khalil Nawaz; Qudeer Ahmad (Arabian Journal of Geosciences, 2021)

Correction to: Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

The effects of some heavy metals on some fish species - Saba Naeem; Muhammad Ashraf; Masroor Ellahi Babar; Sana Zahoor; Shaukat Ali (Environmental Science and Pollution Research, 2021)

An extreme climatic event and systemic vulnerabilities in the face of conflict: insights from the Taliban insurgency in Swat, Pakistan - Muhammad Rafay Muzamil; Petra Tschakert; Bryan Boruff; Babar Shahbaz (Regional Environmental Change, 2021)

Future climatic changes, extreme events, related uncertainties, and policy recommendations in the Hindu Kush sub-regions of Pakistan - Shaukat Ali; Alia Saeed; Rida Sehar Kiani; Sher Muhammad; Firdos Khan; Romaisa Babar; Asif Khan; Muhammad Shahid Iqbal; Muhammad Arif Goheer; Wajid Naseem; Shah Fahad (Theoretical and Applied Climatology, 2021)

Characterization of dimethoate resistance in Oxycarenus hyalinipennis (Costa): resistance selection, cross-resistance to three insecticides and mode of inheritance - Ansa Banazeer; Muhammad Babar Shahzad Afzal; Sarfraz Ali Shad (Phytoparasitica, 2020)

First report of Fusarium equiseti causing stem rot disease of grape (Vitis vinifera L.) in Afghanistan - Nasir Ahmed Rajput; Bakhat Zaman; Chao Huo; JiFen Cao; Muhammad Atiq; Abdul Mubeen Lodhi; Rehana Naz Syed; Babar Khan; Owais Iqbal; Zhijian Zhao (Journal of Plant Pathology, 2020)

Growth, Biomass Production, and Yield Potential of Quinoa (Chenopodium quinoa Willd.) as Affected by Planting Techniques Under Irrigated Conditions - Saif Ali; Muhammad Umer Chattha; Muhammad Umair Hassan; Imran Khan; Muhammad Bilal Chattha; Babar Iqbal; Muzammal Rehman; Muhammad Nawaz; Muhammad Zubair Amin (International Journal of Plant Production, 2020)

The nexus of environmental degradation and technology innovation and adoption: an experience from dragon - Wang Xinmin; Peng Hui; Muhammad Hafeez; Babar Aziz; Muhammad Waqas Akbar; Muhammad Ayzed Mirza (Air Quality, Atmosphere & Health, 2020)

Phenolic Profile and Thermal Stability of Monovarietal Extra Virgin Olive Oils Based on Synchronous Fluorescence Spectroscopy - Hina Ali; Muhammad Azhar Iqbal; Babar Manzoor Atta; Rahat Ullah; Muhammad Bilal Khan (Journal of Fluorescence, 2020)

Application of Fluorescence Spectroscopy in Wheat Crop: Early Disease Detection and Associated Molecular Changes - Babar Manzoor Atta; Muhammad Saleem; Hina Ali; Muhammad Bilal; Muhammad Fayyaz (Journal of Fluorescence, 2020)

Impact of urbanization, economic growth, and population size on residential carbon emissions in the SAARC countries - Muhammad Khalid Anser; Majed Alharthi; Babar Aziz; Sarah Wasim (Clean Technologies and Environmental Policy, 2020)

Isolation and genetic characterization of virulent strains of avian paramyxovirus-1 from multiple avian species in Azad Jammu and Kashmir 2017–2018 - Abid Hussain; Abdul Wajid; Safa Ather; Kashaf Alyas; Muhammad Awais; Muhammad Rizwan Khan; Tanveer Hussain; Masroor Ellahi Babar (Brazilian Journal of Microbiology, 2020)

Spatio-Temporal Variability of Summer Monsoon Onset over Pakistan - Shaukat Ali; Bushra Khalid; Rida Sehar Kiani; Romaisa Babar; Sana Nasir; Nadia Rehman; Muhammad Adnan; Muhammad Arif Goheer (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Spatiotemporal variability in spate irrigation systems in Khirthar National Range, Sindh, Pakistan (case study) - Abdul Ghani Soomro; Muhammad Munir Babar; Muhammad Arshad; Anila Memon; Babar Naeem; Arshad Ashraf (Acta Geophysica, 2020)

Estimation of groundwater potential using GIS modeling in Kohistan region Jamshoro district, Southern Indus basin, Sindh, Pakistan (a case study) - Aneela Memon; Kamran Ansari; Abdul Ghani Soomro; Muhammad Afzal Jamali; Babar Naeem; Arshad Ashraf (Acta Geophysica, 2020)

Synergistic effect of heartwood extracts in combination with linseed oil as wood preservatives against subterranean termite Heterotermes indicola (Blattodea: Rhinotermitidae) - Babar Hassan; Sohail Ahmed; Grant Kirker; Mark E. Mankowski; Muhammad Misbah ul Haq (Environmental Science and Pollution Research, 2020)

Application of water quality index, synthetic pollution index, and geospatial tools for the assessment of drinking water quality in the Indus Delta, Pakistan - Ghulam Shabir Solangi; Altaf Ali Siyal; Muhammad Munir Babar; Pirah Siyal (Environmental Monitoring and Assessment, 2019)

Spinosad resistance selected in the laboratory strain of Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae): studies on risk assessment and cross-resistance patterns - Ansa Banazeer; Muhammad Babar Shahzad Afzal; Mamuna Ijaz; Sarfraz Ali Shad (Phytoparasitica, 2019)

An empirical evaluation of financial development-carbon footprint nexus in One Belt and Road region - Muhammad Hafeez; Chunhui Yuan; Khuram Shahzad; Babar Aziz; Kashif Iqbal; Salman Raza (Environmental Science and Pollution Research, 2019)

Thermal Effects on Biochemical Signatures of UHT, Pasteurized and Domestically Boiled Buffalo Milk Detected by Synchronous Fluorescence Spectroscopy - Hina Ali; Muhammad Saleem; Rahat Ullah; Saranjam Khan; Babar Manzoor Atta; Muhammad Bilal (Journal of Fluorescence, 2019)

Effect of biofertilizers and diatomaceous earth on life and movement of subterranean termites under laboratory conditions - Sohail Ahmed; Babar Hassan; Muhammad Umer Farooq (International Journal of Tropical Insect Science, 2018)

Interaction between PGPR and PGR for water conservation and plant growth attributes under drought condition - Naeem Khan; Asghari Bano; Muhammad Adnan Shahid; Wajid Nasim; MD Ali Babar (Biologia, 2018)

Osteopontin gene polymorphism association with milk traits and its expression analysis in milk of riverine buffalo - Sidra Manzoor; Asif Nadeem; Javed Maryam; Abu Saeed Hashmi; Muhammad Imran; Masroor Ellahi Babar (Tropical Animal Health and Production, 2018)

Performance of CMORPH, TMPA, and PERSIANN rainfall datasets over plain, mountainous, and glacial regions of Pakistan - Yawar Hussain; Frédéric Satgé; Muhammad Babar Hussain; Hernan Martinez-Carvajal; Marie-Paule Bonnet; Martin Cárdenas-Soto; Henrique Llacer Roig; Gulraiz Akhter (Theoretical and Applied Climatology, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Molecular docking and glucosidase inhibition studies of novel N-arylthiazole-2-amines and Ethyl 2-[aryl(thiazol-2-yl)amino]acetates - Ayesha Babar; Muhammad Yar; Hamadeh Tarazi; Vera Duarte; Mohammed B. Alshammari; Mazhar Amjad Gilani; Haffsah Iqbal; Munawwar Ali Munawwar; Maria J. Alves; Ather Farooq Khan (Medicinal Chemistry Research, 2017)

Soil compaction effects on soil health and cropproductivity: an overview - Adnan Noor Shah; Mohsin Tanveer; Babar Shahzad; Guozheng Yang; Shah Fahad; Saif Ali; Muhammad Adnan Bukhari; Shahbaz Atta Tung; Abdul Hafeez; Biangkham Souliyanonh (Environmental Science and Pollution Research, 2017)

Seismic attributes’ application to evaluate the Goru clastics of Indus Basin, Pakistan - Muhammad Naseer Tayyab; Shazia Asim; Muhammad Mass Siddiqui; Muhammad Naeem; Sarfraz Hussain Solange; Farhan Khan Babar (Arabian Journal of Geosciences, 2017)

Studies on genetics, stability and possible mechanism of deltamethrin resistance in Phenacoccus solenopsis Tinsley (Homoptera: Pseudococcidae) from Pakistan - BUSHRA SADDIQ; MUHAMMAD BABAR SHAHZAD AFZAL; SARFRAZ ALI SHAD (Journal of Genetics, 2016)

Osmoregulation and antioxidant production in maize under combined cadmium and arsenic stress - Shakeel Ahmad Anjum; Mohsin Tanveer; Saddam Hussain; Babar Shahzad; Umair Ashraf; Shah Fahad; Waseem Hassan; Saad Jan; Imran Khan; Muhammad Farrukh Saleem; Ali Ahsan Bajwa; Longchang Wang; et al. (Environmental Science and Pollution Research, 2016)

Sediment yield assessment and identification of check dam sites for Rawal Dam catchment - Nida Samad; Muhammad Hamid Chauhdry; Muhammad Ashraf; Muhammad Saleem; Qudsia Hamid; Umair Babar; Hassan Tariq; Muhammad Shahid Farid (Arabian Journal of Geosciences, 2016)

Resistance risk analysis to acetamiprid and other insecticides in Acetamiprid-Selected population of Phenacoccus solenopsis - Mamuna Ijaz; Muhammad Babar Shahzad Afzal; Sarfraz Ali Shad (Phytoparasitica, 2016)

Deltamethrin resistance in the cotton mealybug, Phenacoccus solenopsis Tinsley: Cross-resistance to other insecticides, fitness cost analysis and realized heritability - Bushra Saddiq; Naeem Abbas; Sarfraz Ali Shad; Muhammad Aslam; Muhammad Babar Shahzad Afzal (Phytoparasitica, 2016)

Genetics, realized heritability and preliminary mechanism of spinosad resistance in Phenacoccus solenopsis Tinsley (Homoptera: Pseudococcidae): an invasive pest from Pakistan - Muhammad Babar Shahzad Afzal; Sarfraz Ali Shad; Naeem Abbas (Genetica, 2015)

Characterization of D-genome diversity for tolerance to boron toxicity in synthetic hexaploid wheat and in silico analysis of candidate genes - Muhammad Ilyas; Tariq Mahmood; Ahmad Ali; Muhammad Babar; Awais Rasheed; Abdul Mujeeb-Kazi (Acta Physiologiae Plantarum, 2015)

Synthesis and effect of substituent position on anti-inflammatory activity of 3-(halobenzyl)isocarbostyrils - Tariq Mahmood Babar; Muhammad Moazzam Naseer; Farukh Iftakhar Ali; Nasim Hasan Rama; Taibi Ben Hadda (Medicinal Chemistry Research, 2014)

Erratum to: Effect of varying dietary energy levels during the last trimester of pregnancy on subsequent first lactation performance in Sahiwal heifers - Muhammad Fiaz; Muhammad Abdullah; Muhammad Nasir; Khalid Javed; Masroor Ellahi Babar; Talat Naseer Pasha; Makhdoom Abdul Jabbar (Tropical Animal Health and Production, 2014)

Interactions of ketoamide inhibitors on HCV NS3/4A protease target: molecular docking studies - Abdul Wadood; Muhammad Riaz; Syed Babar Jamal; Masaud Shah (Molecular Biology Reports, 2014)

Polypharmacy (herbal and synthetic drug combination): a novel approach in the treatment of type-2 diabetes and its complications in rats - Rupinder Kaur; Muhammad Afzal; Imran Kazmi; Iqbal Ahamd; Zubair Ahmed; Babar Ali; Sayeed Ahmad; Firoz Anwar (Journal of Natural Medicines, 2013)

Molecular phylogeny of Pakistani riverine buffalo based on genetic variability of mitochondrial cytochrome b gene - Rashid Saif; Muhammad Wasim; Masroor Ellahi Babar (Molecular Biology Reports, 2012)

Effect of varying dietary energy levels during the last trimester of pregnancy on subsequent first lactation performance in Sahiwal heifers - Muhammad Fiaz; Muhammad Abdullah; Muhammad Nasir; Khalid Javed; Masroor Ellahi Babar; Talat Naseer Pasha; Makhdoom Abdul Jabbar (Tropical Animal Health and Production, 2012)

DNA typing of Pakistani cattle breeds Tharparkar and Red Sindhi by microsatellite markers - Amber Azam; Masroor Ellahi Babar; Sehrish Firyal; Aftab Ahmad Anjum; Nabeela Akhtar; Muhammad Asif; Tanveer Hussain (Molecular Biology Reports, 2012)

Prevalence of hepatitis C virus (HCV) genotypes in Balochistan - Sarwat Afridi; Muhammad Naeem; Abid Hussain; Naseebullah Kakar; Masroor Ellahi Babar; Jamil Ahmad (Molecular Biology Reports, 2009)

Expression and identification of folate-sensitive fragile sites in British Suffolk sheep (Ovis aries) - Ahmad Ali; Muhammad Abdullah; Masroor Ellahi Babar; Khalid Javed; Asif Nadeem (Journal of Genetics, 2008)